2008
DOI: 10.1373/clinchem.2007.101451
|View full text |Cite
|
Sign up to set email alerts
|

Joint Effects of Antibody to Heat Shock Protein 60, Hypertension, and Diabetes on Risk of Coronary Heart Disease in Chinese

Abstract: BACKGROUND: Several studies have suggested an association between antibody to human heat shock protein 60 (anti-Hsp60) and coronary atherosclerosis, but the results have been inconsistent. The aim of this study was to investigate the association between anti-Hsp60 and coronary heart disease (CHD) and to determine whether anti-Hsp60, hypertension, and diabetes have joint effects on CHD risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 36 publications
1
15
0
5
Order By: Relevance
“…7 Briefly, systolic blood pressure and fasting glucose in the CHD group were significantly higher than in the control subjects. Total cholesterol levels were significantly lower in CHD case subjects than in control subjects, and this was probably due to the higher incidence of cholesterol-lowering medication use.…”
Section: Characteristics Of Study Populationmentioning
confidence: 94%
See 3 more Smart Citations
“…7 Briefly, systolic blood pressure and fasting glucose in the CHD group were significantly higher than in the control subjects. Total cholesterol levels were significantly lower in CHD case subjects than in control subjects, and this was probably due to the higher incidence of cholesterol-lowering medication use.…”
Section: Characteristics Of Study Populationmentioning
confidence: 94%
“…The study design and subject demographics have been detailed previously. 7 Briefly, patients 40 to 79 years of age were recruited consecutively from 3 hospitals (Tongji Hospital, Union Hospital, and Wugang Hospital) in Wuhan (Hubei, China) between May 2004 and October 2006. The inclusion criteria for the case subjects were stenoses Ն50% in at least 1 major coronary artery by coronary angiography and/or a diagnosis of CHD based on the World Health Organization criteria.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…Many population-based studies showed a strong correlation between ATS and high levels of soluble, circulating HSP60 [62][63][64][65][66] as well as of anti-HSP60 antibodies [65][66][67][68][69]. Both chaperonin and anti-chaperonin antibodies have been shown to elicit production of pro-inflammatory cytokines [59,70,71].…”
Section: Hsp60 and Its Bacterial Counterpart Are Pro-atherogenic Molementioning
confidence: 99%